2019
DOI: 10.15414/jmbfs.2019.8.4.1072-1075
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Variety on the Content of Total Polyphenols and Antioxidant Activity in Leek (Allium Porrum L.)

Abstract: Note: A-B values with different letters mean significant differences (p <0.05) among selected parts of leek; a-h values with different letters mean significant differences (p <0.05) among selected parts and cultivars of leek, values of antioxidant activity are expressed as arithmetic mean

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…However, they did not find a significant relation between TPC and DPPH assay. Contrary to this study, other authors [ 3 ] found a strong and significant correlation between TPC and DPPF both for CR and WH of leek. In our study, we found significant correlations ( p < 0.05) between TPC and EC 50 for ABTS, DPPH and RED (r = −0.809, −0.980, and −0.948, respectively).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, they did not find a significant relation between TPC and DPPH assay. Contrary to this study, other authors [ 3 ] found a strong and significant correlation between TPC and DPPF both for CR and WH of leek. In our study, we found significant correlations ( p < 0.05) between TPC and EC 50 for ABTS, DPPH and RED (r = −0.809, −0.980, and −0.948, respectively).…”
Section: Resultscontrasting
confidence: 99%
“…In the WH of CS, the average TPC was 1.3 µg/mg dm, while in GR it was several-fold higher (50.6 µg/mg dm). Kovarovič et al [ 3 ] also found that GR is characterized by a higher content of total phenolic compared to WH. Our results are lower compared to Kovarovič et al [ 3 ], who found that the content of total phenolics depending on leek variety ranged from 504 to 1117 µg/mg dm, and from 777 to 1224 µg/mg dm for WH and GR, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten accessions of leek originating from regions with different weather were evaluated by Arfa, Najjaa, Yahia, Tlig, and Neffati (2015) and showed phenolic contents ranging from 16 to 21 mg GAE/g; however, Kovarovič et al. (2019) reported contents (from 0.50 to 1.11 mg GAE/g FW) which are in agreement with this study. The great variation observed may be attributed to many factors that could influence the vegetable composition (origin, climate condition, cultivation practices, harvest time), as well as processing methods and extraction procedures.…”
Section: Resultssupporting
confidence: 85%